Women in Paid Employment : A Role for Public Policies and Social Norms in Guatemala - Almeida, Rita K.; Viollaz, Mariana (World Bank, Washington, DC, 2022)
With only 32 percent of working-age women in the labor market, Guatemala is an upper-middle-income country with one of the lowest rates of female labor force participation in the Latin America and the Caribbean region, and in the world. The rate of female labor force participation is especially low in the poor regions of the North and the Northwest. This paper explores information from different micro data sets, including the most recent Population Census (2002 and 2018) to assess the drivers of the recent progress. Between 2002 and 2018, the female labor force participation rate increased 5.7 percentage points, from an average of 26 to 32 percent nationwide. This increase was partly explained by the drastic increases in the educational attainment of women, the reduction in fertility, and the country’s structural transformation toward services. However, a large component remains unexplained. Exploring 2018 data, the paper shows that social norms, attitudes toward women in society, and public policies are important determinants of these changes. The analysis suggests that, taken together, these factors can all become an important source of increased female labor force participation moving forward.